Avaliação da atenção à saúde na experiência de gestantes vivendo com HIV - Kleinubing, Raquel Einloft (2015)
It was set as a goal to compare the quality of health care for pregnant women living with HIV between the types of service, according to the short version PCATool-ADULTO-BRASIL, in the users‟ experience. It is a cross-cut research. The data collection was held from april to november 2014 in the network of Primary Health Care (PHC), of the Academic Hospital of Santa Maria and the Hospital Casa de Saúde in the city of Santa Maria/RS. The Predictive Analytics Software (PASW) version 18.0 for Windows was used for data analysis. The ethic aspects contained in the Resolution 466/12 were observed. The population of this study consisted in 78 women who used the PHC services of the city of Santa Maria/RS during the gestational period in the year of 2012 to 2014. The results set forth the sociodemographic and clinical variables: skin color; housing city; use of antiretroviral medication before and during the pregnancy were significantly associated to the regular care service during the pregnancy. The quality evaluation of the attention to health has shown that the pregnant women living with HIV, in the majority of cases, recognized the PHC as a regular source of care (74,35%). The joint analysis of the attributes according to type of service has revealed general unsatisfying scores for both services, PHC and specialized. The gathered results flag that, even though pregnant women living with HIV do consider the PHC as a regular source of care, they observe the assistance fragility in these services, pointing to the need of structural improvement and development of the PHC, in order to make a structural and developmental betterment of the PHC, so that it can qualify the care of this population.